Dividend Changes and Firm’s Future Earnings with Quadratic Mean Reversion Condition: การเปลี่ยนแปลงเงินปันผลและกำไรในอนาคตของกิจการ ภายใต้เงื่อนไข Mean Reversion แบบควอดราติก - Suksonghong, Karoon (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ ในบริบทที่การรับรู้ข้อมูลข่าวสารของบริษัทจดทะเบียนระหว่างฝ่ายบริหาร และผู้ถือหุ้นมีความไม่เท่าเทียมกัน การเฝ้าติดตามการตัดสินใจทางการเงินของฝ่ายบริหาร เช่น การปรับเปลี่ยนนโยบายปันผล จึงอาจเป็นแนวทางหนึ่งที่ผู้ถือหุ้นสามารถใช้ในการคาดเดามุมมองของผู้บริหารต่อความสามารถในการทำกำไรในอนาคตของกิจการ งานวิจัยนี้ทำการศึกษาความสัมพันธ์ระหว่างการเปลี่ยนแปลงเงินปันผลกับกำไรในอนาคตของกิจการ (Information Content of Dividend Hypothesis) โดยเก็บรวมรวมข้อมูลทุติยภูมิรายปี ประเภท Balanced Panel ของบริษัทที่จดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย ตั้งแต่ปี พ.ศ. 2553-2562 และนำเสนอแบบจำลองเศรษฐมิติที่สามารถควบคุมเงื่อนไข Mean Reversion ของกำไร ทั้งในรูปแบบฟังก์ชันเชิงเส้น และฟังก์ชันควอดราติก เพื่อแก้ไขปัญหาความเอนเอียงของผลการศึกษา (Omitted Variable Bias) ซึ่งเป็นประเด็นสำคัญที่ถูกละเลยโดยงานวิจัยในอดีต การศึกษานี้ใช้วิธีประมาณค่าสัมประสิทธิ์ของแบบจำลองด้วยวิธี Fixed-effect Panel OLS ซึ่งผลการศึกษาพบหลักฐานที่สนับสนุนว่า การเปลี่ยนแปลงของกำไรมีพฤติกรรม Mean Reversion ในรูปแบบฟังก์ชันควอดราติก โดยผลการศึกษาจากแบบจำลองควอดราติกนั้น สนับสนุนทฤษฎี Dividend Irrelevant กล่าวคือ ฝ่ายบริหารมิได้ใช้การเปลี่ยนแปลงเงินปันผลเพื่อส่งสัญญาณสะท้อนแนวโน้มกำไรในอนาคตของกิจการต่อผู้ถือหุ้น ดังนั้นนักลงทุนจึงควรเพิ่มความระมัดระวังหากเลือกใช้การเปลี่ยนแปลงนโยบายปันผลเป็นเครื่องมือในการพยากรณ์กำไรในอนาคตของกิจการ นอกจากนั้นนัยยะของผลการศึกษานี้ยังเพิ่มหลักฐานสนับสนุนแนวคิดประสิทธิภาพของตลาดหลักทรัพย์ในระดับกลาง และธรรมาภิบาลของบริษัทจดทะเบียนอีกด้วย ABSTRACT In the context of asymmetric information existing between executives and shareholders, monitoring a financial decision making of executives such as changing a dividend policy can possibly be a clue for anticipating executives’ perspective toward the firm’s future earnings. This study examines the association between the change in dividend and future earnings, the so-called “information content of dividend hypothesis”, by collecting the secondary data of the firms listed in the Stock Exchange of Thailand. The annual data between 2010 and 2019 were structured into the balanced panel format. The econometric models allowing for capturing the mean reversion conditions in both linear and quadratic forms were introduced to overcome the issue of omitted variable bias that was neglected by previous studies. The employed models were estimated using the fixed-effect panel OLS method. The obtained results revealed that earnings of the sample of listed firms are, in fact, follow the quadratic-function mean reversion process. Besides, the results estimated from the quadratic model provide the evidence supporting the dividend irrelevant theory implying that executives change the dividend policy with no intention to signal or reflect the firm’s future earnings prospects. Therefore, predicting firm’s future earnings with information of changes in dividend should be executed with caution. The results also support the notion of semi-strong form market efficiency as well as the good governance of listed company.